2017
DOI: 10.1007/s10754-017-9223-y
|View full text |Cite
|
Sign up to set email alerts
|

Health expenditure and growth dynamics in the SADC region: evidence from non-stationary panel data with cross section dependence and unobserved heterogeneity

Abstract: This paper investigates the long run relationship between health care expenditure and economic growth, using panel data for 14 Southern African Development Community (SADC) member countries over the period 1995-2012. The non-stationarity and cointegration properties between health expenditure per capita and GDP per capita were examined, controlling for cross section dependence and heterogeneity between countries. Our results suggest that health expenditure and GDP per capita are non-stationary and cointegrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
6
18
0
Order By: Relevance
“…The estimation results in Table 3 are overall in line with the wider literature on economic growth as well as health economics. In particular, they are consistent with the findings of Kouassi et al (2018) and Piabuo and Tieguhong (2017) that there is a long run positive relationship between health expenditures and economic growth for countries in the Economic Community of Central African States (ECCAS) subregion and for countries in the Southern African Development Community (SADC), respectively. The results also confirm the findings in the literature that health outcomes matter for economic growth.…”
Section: Estimation Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The estimation results in Table 3 are overall in line with the wider literature on economic growth as well as health economics. In particular, they are consistent with the findings of Kouassi et al (2018) and Piabuo and Tieguhong (2017) that there is a long run positive relationship between health expenditures and economic growth for countries in the Economic Community of Central African States (ECCAS) subregion and for countries in the Southern African Development Community (SADC), respectively. The results also confirm the findings in the literature that health outcomes matter for economic growth.…”
Section: Estimation Results and Discussionsupporting
confidence: 87%
“…Elmi and Sadeghi (2012) show that economic growth and health spending have a bilateral causality and long-run relationship in developing countries during the 1990-2009 period. In the same vein, Kouassi et al (2018), in a panel data analysis for 14 Southern African Development Community (SADC) countries over the period 1995-2012, find that health expenditure and GDP per capita are cointegrated. Bloom et al (2001Bloom et al ( , 2004 are among seminal papers that provide strong empirical evidence in favor of health as well as demographic variables in determining economic growth.…”
Section: Health Expenditures and Economic Growthmentioning
confidence: 92%
See 1 more Smart Citation
“…This study provided same findings as prior literature (Blackbrun and Cipriani, 2002;Asia and Pueyo, 2006;Desborders, 2011; Halici-Tuluce et al , 2016; Kouassi et al , 2018). In the countries with relatively young populations, the decrease in the mortality rate of the youth and the change in the expectations of lifelong benefit positively affect the investment decisions of the human capital, and thus, a positive effect on growth occurs.…”
Section: Discussionsupporting
confidence: 89%
“…This situation has been explained by the fact that private health expenditures were low in low-income countries' GDP or they were caused by the negative effects of these expenditures on fixed capital investments. Kouassi et al (2018) studied the relationship between the health expenditures and economic growth of the South African Development Community (SADC) member country with panel data methodology for 1995–2012 period. The findings showed that health expenditures and GDP had a cointegrated relationship and health services in the SADC region are a compulsory commodity.…”
Section: Health and Growth Nexusmentioning
confidence: 99%